CORRELATION OF MICROALBUMINURIA WITH AGE, DURATION, GLYCATED HEMOGLOBIN, BLOOD SUGAR LEVELS, BLOOD PRESSURE AND RENAL PARAMETERS OF TYPE 2 DIABETES PATIENTS - P, Geetha; P, Shanmugasundaram (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: Microalbuminuria is the strongest predictor of diabetic nephropathy, which is the main cause of morbidity and mortality. The aim of the study is to determine the prevalence of microalbuminuria in Type 2 diabetes patients and to evaluate the relation between the microalbuminuria and age, duration, glycated hemoglobin (HbA1c), blood sugar levels, blood pressure (BP), and renal parameters of Type 2 diabetes patients. Methods: The prospective study includes 115 patients with Type 2 diabetes, visiting in outpatient diabetes hospital, Chennai. The case reports of the patients diagnosed with blood sugar, HbA1c level BP and renal parameters of Type 2 diabetes patients were recorded and compared with microalbuminuria. Statistical analysis was carried out using student t-test and Pearson correlation. Results: The study revealed that the prevalence of microalbuminuria in this study was 27.82%. Incidence of microalbuminria increases with age, duration of diabetes, blood sugar levels, and hypertension. There is no association of body mass index and sex on the prevalence of microalbuminuria in Type 2 diabetes mellitus. Creatinine clearance has shown a weak negative correlation with microalbuminuria in our study. Conclusion: The present study showed that there is a weak positive correlation of microalbuminuria with blood sugar levels, duration and systolic BP. There is a weak negative correlation of creatinine shows that impairment in the kidney function.